A food first approach to carbohydrate supplementation in endurance exercise: a systematic review - Reynolds, K. M.; Clifford, T.; Mears, S. A.; James, L. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
This systematic review analyzed whether carbohydrate source (food vs. supplement) influenced performance and gastrointestinal (GI) symptoms during endurance exercise. Medline, SPORTDiscus, and citations were searched from inception to July 2021. Inclusion criteria were healthy, active males and females aged >18 years, investigating endurance performance, and GI symptoms after ingestion of carbohydrate from a food or supplement, <60 min before or during endurance exercise. The van Rosendale scale was used to determine risk of bias, with seven studies having low risk of bias. A total of 151 participants from 15 studies were included in the review. Three studies provided 0.6-1 g carbohydrate/kg body mass during 5-45 min precycling exercise (duration 60-70 min) while 12 studies provided 24-80 g/hr carbohydrate during exercise (60-330 min). Except one study that suggested a likely harmful effect (magnitude-based inferences) of a bar compared to a gel consumed during exercise on cycling performance, there were no differences in running (n = 1) or cycling (n = 13) performance/capacity between food and supplemental sources. Greater GI symptoms were reported with food compared with supplemental sources. Highly heterogenous study designs for carbohydrate dose and timing, as well as exercise protocol and duration, make it difficult to compare findings between studies. A further limitation results from only one study assessing running performance. Food choices of carbohydrate consumed immediately before and during endurance exercise result in similar exercise performance/capacity responses to supplemental carbohydrate sources, but may slightly increase GI symptoms in some athletes, particularly with exercise >2 hr.